Desensitisation of neutrophil responses by systemic interleukin 8 in cystic fibrosis. - Dai, Y. (1994)
BACKGROUND--Inflammation associated with neutrophil infiltration is a commonly observed feature of children with cystic fibrosis. Production of the major neutrophil chemotactic cytokine interleukin 8 (IL-8) is potentially of great importance in the pathology of cystic fibrosis. Concentrations of IL-8 in both sputum and bronchoalveolar lavage fluid have been found to be higher in children with cystic fibrosis than in controls. The IL-8 induced chemotactic response and numbers of IL-8 receptors on peripheral neutrophils obtained from children with cystic fibrosis have been compared with a control group of children. METHODS--Cells were isolated from 18 patients with cystic fibrosis (aged 4-20 years) and 13 controls (aged 5-12 years) by dextran centrifugation followed by separation on Lymphoprep. Chemotaxis was assayed using multiwell microchemotaxis chambers and 5 microns polycarbonate filters. Filters were fixed and stained with Haema-Gurr for counting. Results were expressed as numbers of neutrophils per high power field (HPF). RESULTS--At the optimum concentration (1 x 10(-8) mol/l) the number of cells migrating were similar for controls (150 (12)/HPF) and for the cystic fibrosis group (140 (14)/HPF)). At lower concentrations the numbers of neutrophils migrating were lower for the cystic fibrosis group. Scatchard analysis of 125I-labelled IL-8 binding revealed lower numbers of receptors on neutrophils from patients with cystic fibrosis (22,000 per cell) than from controls (75,000 per cell). CONCLUSIONS--Reduced responsiveness to IL-8 of neutrophils from patients with cystic fibrosis is associated with receptor desensitisation as a result of exposure to high systemic levels of IL-8.